Renal Dysfunction Predicts Major Adverse Cardiovascular Events in Black and Latino Patients Who have Atrial Fibrillation - Zeeshan, Muhammad; Lehman, Erik B.; Naccarelli, Gerald V.; Ahmad, Tariq Ali; Ayinla, Raji; Bhatnagar, Sudhanshu (Cardiology and Cardiovascular Medicine, 2023)
Background: Atrial Fibrillation (AF) is present in over 6 million Americans. However, AF occurs less commonly in African Americans and Latinos compared to Caucasians. Major adverse cardiovascular events (MACE) is the leading cause of death in these populations. Hypothesis: We theorize that glomerular filtration rates (GFR) is an independent risk factor for MACE in African Americans and Latinos with non-valvular AF (NVAF). Methods: The association of reduced GFR with MACE in NVAF patients was investigated by retrospective chart review. 656 patients were included: 339 with GFR <60 and 317 with GFR ≥60. A Chi-square test, two-sample t-test, or Wilcoxon Rank Sum test was used to test for differences between the two groups in terms of demographic variables and other risk factors. The association between GFR groups and myocardial infarction (MI), stroke, and/or death, was tested using binomial logistic regression. To incorporate the element of time and adjust for covariates, a Cox proportional hazards model analysis was applied for each outcome variable. Results: As compared to GFR ≥60, a GFR <60 in NVAF was an independent risk factor for MI (HR 1.88 (1.17, 3.04); p=0.009); death (HR 1.63 (1.11, 2.41); p=0.014) and MI, stroke or death ((HR 1.37 (1.05, 1.78); p=0.018). GFR <60 was not an independent risk factor for stroke (HR 1.13 (0.77, 1.65); p=0.529). Conclusion: Renal dysfunction in patients with NVAF is an independent risk factor for MI, death in and composite of MI, stroke and death in African American and Latino populations.